2018
DOI: 10.3390/md16010031
|View full text |Cite
|
Sign up to set email alerts
|

Specific Molecular Signatures for Type II Crustins in Penaeid Shrimp Uncovered by the Identification of Crustin-Like Antimicrobial Peptides in Litopenaeus vannamei

Abstract: Crustins form a large family of antimicrobial peptides (AMPs) in crustaceans composed of four sub-groups (Types I-IV). Type II crustins (Type IIa or “Crustins” and Type IIb or “Crustin-like”) possess a typical hydrophobic N-terminal region and are by far the most representative sub-group found in penaeid shrimp. To gain insight into the molecular diversity of Type II crustins in penaeids, we identified and characterized a Type IIb crustin in Litopenaeus vannamei (Crustin-like Lv) and compared Type II crustins … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
28
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(29 citation statements)
references
References 43 publications
1
28
0
Order By: Relevance
“…Although unusual, the presence of Type IIa crustins has been reported for other decapod crustaceans from the Pleocyemata suborder (59,60). On the other hand, Type IIb crustins were only described in penaeid shrimp species (46).…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…Although unusual, the presence of Type IIa crustins has been reported for other decapod crustaceans from the Pleocyemata suborder (59,60). On the other hand, Type IIb crustins were only described in penaeid shrimp species (46).…”
Section: Discussionmentioning
confidence: 92%
“…Comparatively, crustin members from Types III and IV are composed of one and two WAP domains, respectively, and are devoid of any other domains. Interestingly, while Type I crustins are widely distributed across decapod crustaceans (Pleocyemata and Dendrobranchiata), Type II crustins (Sub-Types IIa and IIb) are mainly present in penaeid shrimps (Dendrobranchiata) (46).…”
Section: Introductionmentioning
confidence: 99%
“…Unlike ALFs, the antibacterial activities of PENs are essentially directed against Gram-positive bacteria (Destoumieux et al, 1999). Crustins form a large family of antimicrobial peptides, exhibiting protease inhibitory properties and regulatory functions in bacterial growth to all microbes (Barreto et al, 2018). The C-MnSOD and lysozymes are immune effector proteins that have antibacterial activities (Niu et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…The nodes with the greatest number of neighbors were identified (Table 3), which could be considered significant hubs of the network. Some important keystone genes, such as ALF-D, CrustinA and Lvserpin (Nigou et al, 2013;Liu et al, 2014;Barreto et al, 2018), have been reported to play central roles in antimicrobial activities. PCoA was performed to determine the transcript profiles across groups.…”
Section: Transcriptome Difference Between Control and Wfsmentioning
confidence: 99%
“…Instead, the expression of ALFs from Groups A, B, D and G was quite similar to that observed for other shrimp AMPs that are exclusively produced by hemocytes [ 16 ]. On the one hand, the expression of ALFs early in development could be the result of maternal transmission [ 16 , 22 ] but, on the other hand, those transcripts might originate from other shrimp tissues. Interestingly, in different species, including L. vannamei , the expression of ALFs from Groups C and F was mainly detected in other tissues (digestive system, gills, eyestalk) than in the circulating hemocytes [ 17 , 18 , 19 ].…”
Section: Discussionmentioning
confidence: 99%